PEMBENTUKAN PERILAKU KONSUMEN DALAM TREN #RACUNTIKTOK: ANALISIS NETNOGRAFI PADA KONTEN DAN KOMENTAR TERKAIT PARFUM DI TIKTOK - Paujiatul Arifah; Ocvita Ardhiani; Reni Fitriani (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
Digital marketing continues to evolve alongside the expansion of social media, which is increasingly saturated with marketing messages. The short-form video format has positioned TikTok as an effective platform for contemporary marketing. One trend that remains widely adopted among TikTok users is marketing content that incorporates the hashtag #RacunTikTok. The interaction patterns within this trend guided this study to identify recurring patterns that reflect specific forms of consumer behavior. This study employs the Message Design Logic theory proposed by Daniel O’Keefe (1998). The concept of consumer behavior is categorized through thematic analysis to refine the research focus. The themes identified in the comment sections include FOMO (fear of missing out), impulsive buying, trust and validation, and skepticism. This research adopts a qualitative approach using netnographic analysis. The researcher conducted non-participant observation by selecting five TikTok contents featuring the hashtag #RacunTikTok, specifically related to perfume brands. Additional hashtags such as #RacunTikTokShop, #RacunCiMon, and #RacunParfume were also included, based on the consideration that the keyword “Racun” remains consistent across these variations. The findings indicate that marketing content using the #RacunTikTok hashtag for perfume products predominantly employs rhetorical logic. In the comment sections, themes of trust and validation appear most frequently, followed by a substantial number of skeptical responses, indicating that audiences maintain a critical stance. In conclusion, the #RacunTikTok phenomenon functions not only as a communication strategy employed by content creators, but also facilitates interactions among audiences that collectively construct legitimacy and influence consumer behavior on social media. Keyword: #RacunTikTok, TikTok Trends, Social Media, Netnographic, Consumer Behavior.